A Phase II Study with Lead‐In Safety Cohort of 5‐Fluorouracil, Oxaliplatin, and Lapatinib in Combination with Radiation Therapy as Neoadjuvant Treatment for Patients with Localized HER2‐Positive Esophagogastric Adenocarcinomas. (1st August 2017) - Shepard, Gregg; Arrowsmith, Edward R.; Murphy, Patrick; Barton, John H.; Peyton, James D.; Mainwaring, Mark; Blakely, Laura; Maun, Noel A.; Bendell, Johanna C.
Abstract: Lessons Learned : Neoadjuvant 5‐fluorouracil, oxaliplatin, and lapatinib in combination with radiation therapy is safe for neoadjuvant treatment for patients with localized human epidermal growth receptor 2‐positive esophagogastric adenocarcinoma. Evaluation of this drug combination in a larger patient pool would allow for more accurate analysis of its efficacy. Background: The optimal design of neoadjuvant chemoradiation for the treatment of localized esophagogastric cancers is the subject of much debate. In this nonrandomized trial, we evaluated neoadjuvant 5‐fluorouracil (5‐FU), oxaliplatin, and lapatinib in combination with radiation therapy as neoadjuvant treatment for patients with localized human epidermal growth receptor 2 (HER2)‐positive esophagogastric adenocarcinomas. Methods: Patients received neoadjuvant 5‐FU (225 mg/m 2 continuous intravenous infusion, days 1–42), oxaliplatin (85 mg/m 2 intravenously [IV], days 1, 15, and 29), and lapatinib (six patients, 1, 000 mg p.o., days 1–42; six patients, 750 mg p.o., days 1–42) plus radiation (1.8 Gy/day Monday through Friday for 50.4 Gy total). Following restaging, eligible patients underwent definitive resection, and pathologic response to neoadjuvant therapy was assessed. Planned enrollment was 42 patients. The primary endpoint was the pathologic complete response (pCR) rate. Results: Twelve patients (median age 64 years; 67% male) received a median of 5.6 weeks of treatment (range: 1.1–8.4). The pCR rate was 8%; four of the 12 patients underwent tumor resection and one patient had a pCR, with pathologic partial response in the remaining three. The most common lapatinib‐related adverse events included (all grades) nausea (67%) and diarrhea (58%), although these were all grade 1 or 2. Enrollment was halted due to low accrual. Conclusion: The treatment regimen was determined to be safe. The study was terminated early due to low accrual.